Studies on Antimicrobial, Antibiofilm, Efflux Pump Inhibiting, and ADMET Properties of Newly Synthesized 1,3,4‐Thiadiazole Derivatives** - Zurnacı, Merve; Şenturan, Merve; Şener, Nesrin; Gür, Mahmut; Altınöz, Eda; Şener, İzzet; Altuner, Ergin Murat (Wiley, 2021)
Abstract The novel compounds bearing 1,3,4‐thiadiazole moiety were obtained and their structures were identified using FT‐IR, NMR methods, elemental, and mass analysis. UV‐Vis and fluorescence spectra were obtained in six different polarity solvents. In addition, antimicrobial, antibiofilm, and the efflux pump inhibiting activities of the new compounds on K. pneumoniae , methicillin‐resistant S. aureus (MRSA), E. coli , and C. albicans were investigated. Furthermore, druglikeness and ADMET properties of the compounds were determined. As a result, it was observed that some of the derivatives presented antimicrobial activity against K. pneumoniae , S. aureus , and C. albicans . But the MBC/MFC test showed that all the activities were bacteriostatic. In addition, these derivatives have the potential of using both inhibiting and activating biofilm formation depending on the concentration. 1,3,4‐thiadiazole derivatives also presented good efflux pump inhibition in K. pneumoniae and E. coli . ADMET tests showed that 1,3,4‐thiadiazole derivatives have the potential of being used as therapeutic compounds.